PERAN LIVE STREAMING DALAM MENINGKATKAN KEPUTUSAN PEMBELIAN PRODUK PADA APLIKASI TIKTOK SHOP STUDI PADA MAHASISWA ANGKATAN 2020 - Khoerul Ambiya; Syifa Pramudita Faddila (Marketgram Journal, 2023)
Digital marketing in Indonesia has enormous potential, because many consumers have switched to the digital world. The purpose of this study was to determine the role of live streaming in improving purchasing decisions on the tiktik shop application. The method used is a quantitative method. Data analysis used simple linear regression analysis. The results of the study show that Live Streaming has a significant influence on Purchase Decisions in the Tiktok Shop Application. Live Streaming has a Positive Correlation to Purchase Decisions at the Tiktok Shop